Implementasi Metode Fuzzy Sebagai Sistem Kontrol Kepekatan Nutrisi Otomatis Tanaman Hidroponik Berbasis Mikrokontroler Pasa Rangkaian Nutrient Film Technique (NFT) - Kurniawan Dwi Yulianto; Achmad Maududie; Nova El Maidah (INFORMAL: Informatics Journal, 2022)
Hydroponics is a method of cultivating plants by utilizing water as a growth medium by emphasizing on meeting the nutritional needs of hydroponic plants. Hydroponics requires special treatment such as maintaining nutrient levels within the range so that the use of a control system is used. The implementation of the automatic nutrition control system aims to make it easier for farmers to regulate the mixing of AB mix + POC nutrients with water at the PPM value of lettuce plants automatically based on the age of plant growth, so that farmers can produce plants with optimal growth and maximum yields. The hydroponic nutrition control system uses the Fuzzy method. The system will also be integrated with the Arduino Uno microcontroller which is equipped with a Total Dissolved Solids (TDS) sensor. The results of this study can be seen that the success of the system can work well in detecting nutrients in the reservoir and can control pumps and water pumps in low, normal, and high conditions. The sensor used can also work well, where the TDS sensor has an error value of 4.81% and then calibration is carried out so that it gets the equation for the TDS value